1981
DOI: 10.1007/bf02032499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium and copper on the ultrastructure ofAnkistrodesmus braunii andAnabaena 7120

Abstract: The effects of brief exposure to, or growth in the presence of, lethal and sublethal concentrations of Cu(NO)2 and Cd(NO3) on the ultrastructure of the blue-green algaAnabaena 7120 and the green algaAnkistrodesmus braunii were studied. Exposure to increasing amount of both metal ions led to the appearance of larger proportions of electron-dense cells whose organelles were less well defined than those of untreated cells. Metal-treated cells ofAnabaena 7120 became distorted. Some had a corrugated appearance. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Microscopic examination suggested that the greater binding ability of the sensitive culture may have been due to release of intracellular substances after lysis. Such lysis was observed earlier with another Anabaena strain [26].…”
Section: Role Of Extraceuular Bindingmentioning
confidence: 70%
“…Microscopic examination suggested that the greater binding ability of the sensitive culture may have been due to release of intracellular substances after lysis. Such lysis was observed earlier with another Anabaena strain [26].…”
Section: Role Of Extraceuular Bindingmentioning
confidence: 70%
“…This significant decrease with phosphate deprivation and metal exposure is consistent with the idea that metabolic processes are reduced under adverse conditions and cells may become dormant. Massalski et al (1981) reported an increase in intrathylakoid space with copper treatment. Changes in vacuole volume, presumably a result (Tables 1-9) of changes in membrane permeability (Sicko-Goad 1982), were evident in Scenedesmus.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these metals are required for the function of respiratory, photosynthetic, and nitrogen-assimilating complexes, their intracellular level and thereby their uptake have to be tightly controlled, as they pose a risk for oxidative stress (50). The presence of about 1 mM iron (29) or about 10 M copper in medium (7,33) largely impairs the growth of Anabaena sp. Not only intoxication but also starvation is a danger for cyanobacteria.…”
Section: Filamentous Cyanobacteria Like Anabaena Sp (Also Known Asmentioning
confidence: 99%